Fabrication of micro- and submicrometer silver patterns by microcontact printing of mercaptosilanes and direct electroless metallization - Mondin, Giovanni; Schumm, Benjamin; Fritsch, Julia; Grothe, Julia; Kaskel, Stefan (Microelectronic Engineering, 2013)
A novel method for the fabrication of silver micro- and submicrometer patterns on glass substrates is reported. Microcontact printing is used to selectively print 3-mercaptopropyltriethoxysilane (MPTES) molecules on glass substrates. No further activation or sensitization step is required for subsequent metallization processes. Electroless plating is used to selectively plate silver on the MPTES-printed areas, leading to selective deposition of silver and the formation of well defined and arbitrary metallic patterns. Several silver structures of various shapes and sizes and lateral dimensions down to 500 nm are fabricated on areas as large as 1 cm2. This very simple, lithography-free and etchant-free patterning method can be used to fabricate any planar silver pattern with resolution down to the submicron scale, with various applications in microelectronics and opto-electronics such as wiring of printed circuits and the fabrication of transparent electrodes in solar cells and displays. © 2012 Elsevier B.V. All rights reserved.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Electroless plating; Mercaptosilane; Metallization; Microcontact printing; Patterning; Silver